From molecules to neural morphology: understanding neuroinflammation in autism spectrum condition. Issue 1 (December 2016) - Young, Adam; Chakrabarti, Bhismadev; Roberts, David; Lai, Meng-Chuan; Suckling, John; Baron-Cohen, Simon
Abstract Growing evidence points toward a critical role for early (prenatal) atypical neurodevelopmental processes in the aetiology of autism spectrum condition (ASC). One such process that could impact early neural development is inflammation. We review the evidence for atypical expression of molecular markers in the amniotic fluid, serum, cerebrospinal fluid (CSF), and the brain parenchyma that suggest a role for inflammation in the emergence of ASC. This is complemented with a number of neuroimaging and neuropathological studies describing microglial activation. Implications for treatment are discussed.